Using host-mimicking conditions and a murine cutaneous abscess model to identify synergistic antibiotic combinations effective against Pseudomonas aeruginosa - Lyons, Nikita; Wu, Weihui; Jin, Yongxin; Lamont, Iain L.; Pletzer, Daniel (Frontiers in Cellular and Infection Microbiology, 2024)
Antibiotic drug combination therapy is critical for the successful treatment of infections caused by multidrug resistant pathogens. We examined investigated the efficacy of combinatorial βlactam and β-lactam/β-lactamase inhibitor combinations treatment with other antibiotics, against the hypervirulent, ceftazidime/avibactam resistant Pseudomonas aeruginosa Liverpool epidemic strain (LES) B58. Although minimum inhibitory concentrations in vitro differed by up to eighty-fold between standard and host-mimicking media, combinatorial effects only marginally changed between conditions for some combinations. Effective combinations in vitro were further tested in a chronic, high-density murine infection model. Colistin and azithromycin showed demonstrated combinatorial effects with ceftazidime and ceftazidime/avibactam both in vitro and in vivo. Conversely,, while tobramycin and tigecycline showed exhibited strong synergy in vitro, this but had no effect was not observed in vivo. Our approach of using host-mimicking conditions and a sophisticated animal model to test evaluate drug synergy to tackleagainst antibiotic resistantbacterial pathogens represents a promising approach. This methodology may mightoffer insights be a first step towards improved into the prediction of combination therapy outcomes and the identification of potential prediction of drug combination success or antibiotic combinatorial treatment failures.